Analysis of Reading Ability in Terms of Parenting Patterns in Grade I Students (Case Study in Elementary School Gugus V Seririt District 2022/2023 Academic Year) - Kadek Agung Sugi Aryawan; I Gusti Agung Ayu Wulandari; I Wayan Sujana (Universitas Pendidikan Ganesha, 2021)
The problem in this study is that the reading ability experienced by grade I students is still low. Teachers at school have provided maximum guidance at school, but students not only learn at school, but students can also learn at home with their parents. Students have more time studying at home with parental guidance than when they study at school. The form of parenting applied by parents greatly affects the development of children, especially in terms of reading. This study aims to determine the factors that influence the reading ability of grade I students and the form of parenting applied by parents at home case study in SD Gugus V, Seririt District, Buleleng Regency. This type of research is descriptive qualitative research using the case study method. The sample determination used purposive sampling technique with a total sample size of 7 student subjects and 7 student parent subjects. Data collection used non-test methods in the form of observation, interviews, questionnaires, and documentation. The data analysis technique uses 2 techniques, namely qualitative descriptive analysis and quantitative description analysis. The results of the data analysis of this study found that the percentage score on the factors that influence reading ability in both aspects is described as follows: 1) internal factors with a percentage score of 69%, and 2) external factors with a percentage score of 72%. Meanwhile, the score of parenting patterns in the three aspects is different. Each aspect is described as follows: 1) authoritarian parenting has a percentage score of 65%, 2) democratic parenting has a percentage score of 78%, and 3) permissive parenting has a percentage score of 66%. From these results, it can be concluded that most parents have applied democratic parenting in educating their children, but the factors that greatly affect the reading ability of most students are external factors.